STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGATASI HAMBATAN PEMANFAATAN TIK DAN MENINGKATKAN KOMPETENSI GURU DI SD - Tria Nur Qana’ah; Ahmad Suriansyah; Arta Mulya Budi Harsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Issues with infrastructure and a lack of qualified staff members are common roadblocks to digital transformation in primary schools. This research seeks to delve into the leadership tactics used by school principals at SDN Karang Mekar 1 Banjarmasin to address obstacles to the utilization of ICT and enhance teachers' digital capabilities. A qualitative method based on a case study design is used in this investigation. Both participant and non-participant observation were used to gather data. The principal served as the policymaker and the teachers as the technical implementers; both roles were represented in the study subjects. Time inefficiency owing to temporary projection equipment and a digital gap between young and older instructors were identified as the biggest hurdles to ICT deployment, according to the findings. To get around this, the principal put a